2014
DOI: 10.1177/0741932514561865
|View full text |Cite
|
Sign up to set email alerts
|

A Group Contingency Plus Self-Management Intervention Targeting At-Risk Secondary Students’ Class-Work and Active Engagement

Abstract: The purpose of the present study is to show that an independent group contingency (GC) combined with self-management strategies and randomized-reinforcer components can increase the amount of written work and active classroom responding in high school students. Three remedial reading classes and a total of 15 students participated in this study. Students used self-management strategies during independent reading time to increase the amount of writing in their reading logs. They used self-monitoring strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
(82 reference statements)
2
17
0
Order By: Relevance
“…Taken together, these findings suggest that students who engage in moderate levels of disruptive behaviors may respond to class‐wide interventions more readily than students with more intense behavior needs. This further supports previous research in which students with higher behavioral needs respond slower to class‐wide self‐management interventions (e.g., Hoff & Ervin, ; Trevino‐Maack, Kamps, & Wills, ). The reduction in disruptive behavior for three of the students during the final intervention condition seems to support this hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, these findings suggest that students who engage in moderate levels of disruptive behaviors may respond to class‐wide interventions more readily than students with more intense behavior needs. This further supports previous research in which students with higher behavioral needs respond slower to class‐wide self‐management interventions (e.g., Hoff & Ervin, ; Trevino‐Maack, Kamps, & Wills, ). The reduction in disruptive behavior for three of the students during the final intervention condition seems to support this hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Although no studies included in Little and colleagues’ () meta‐analysis evaluated the effect of independent group contingencies on academic engagement behavior, other studies have suggested that they may effectively increase student engagement (e.g., Conklin, ; Thorne & Kamps, ; Trevino‐Maack et al., ). Thorne and Kamps () investigated the effects of an independent group contingency on academic engagement and problem behavior in four elementary school classrooms.…”
Section: Independent Group Contingenciesmentioning
confidence: 99%
“…Similarly, Trevino‐Maack and colleagues () used an independent group contingency procedure in conjunction with self‐management to promote academic engagement. Students in three high school remedial reading classes were included in the study.…”
Section: Independent Group Contingenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown self-monitoring to improve academic performance in middle and high school settings including (a) reading comprehension (Alfassi, 1998;Kozminsky & Kozminsky, 2001), (b) accuracy in reading and math assignments (Cancio, West, & Young, 2004;Shimabukuro, Prater, Jenkins, & Edelen-Smith, 1999), and (c) increased productivity in writing (Trevino-Maack, Kamps, & Wills, 2014). Self-monitoring interventions have been shown to improve behaviors that contribute to progressing in school such as lesson and task completion 596134P BIXXX10.1177/1098300715596134Journal of Positive Behavior InterventionsClemons et al (Foley & Epstein, 1993;Koegel, Harrower, & Koegel, 1999;Seabaugh & Schumaker, 1994).…”
mentioning
confidence: 99%